Telomerase activity in non-small cell lung cancer - Dobija-Kubica, Katarzyna; Zalewska-Ziob, Marzena; Bruliński, Krzysztof; Rogoziński, Paweł; Wiczkowski, Andrzej; Gawrychowska, Agata; Gawrychowski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : High telomerase activity has been detected in the majority of malignant neoplasms including lung cancer. The purpose of the study was to attempt to use telomerase activity as a prognostic factor in patients with non-small cell lung cancer (NSCLC). Material and methods : Telomerase activity was analyzed in 47 tissue specimens taken from patients with NSCLC. The control group consisted of 30 specimens of non-cancerous lung parenchyma. Telomerase activity was measured by means of the telomeric repeat amplification protocol (TRAP). Results : Telomerase activity in the neoplastic tissue was significantly higher than in the lung parenchyma that was free from neo-plastic infiltration. There was no significant association between telomerase activity and age, gender, tobacco smoking, histological type of the tumor, or staging (pTNM). No association was found between the level of telomerase activity in NSCLC specimens and the two-year survival rate of patients (p = 0.326). A higher level of telomerase activity in poorly differentiated tumors (G3) as compared to moderately differentiated tumors (G2) was detected (p = 0.008). A positive association was identified between telomerase activity in pulmonary parenchyma free from tumor infiltration and the presence of leukocyte infiltration (p = 0.0001). Conclusions: No association was found between the level of telomerase activity in NSCLC specimens and the two-year survival rate of patients. The study has revealed a positive association between telomerase activity and the grade of differentiation (G) in NSCLC.